Prevention and control of COVID-19 in nursing homes, orphanages, and prisons. (November 2020) - Wang, Jiao; Yang, Wenjing; Pan, Lijun; Ji, John S.; Shen, Jin; Zhao, Kangfeng; Ying, Bo; Wang, Xianliang; Zhang, Liubo; Wang, Lin; Shi, Xiaoming
Abstract: As the number of Coronavirus Disease (2019) (COVID-19) cases increase globally, countries are taking more aggressive preventive measures against this pandemic. Transmission routes of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) include droplet and contact transmissions. There are also evidence of transmission through aerosol generating procedures (AGP) in specific circumstances and settings. Institutionalized populations without mobility and living in close proximity with unavoidable contact are especially vulnerable to higher risks of COVID-19 infection, such as the elderly in nursing homes, children in orphanages, and inmates in prisons. In these places, higher prevention and control measures are needed. In this study, we proposed prevention and control strategies for these facilities and provided practical guidance for general measures, health management, personal protection measures, and prevention measures in nursing homes, orphanages, and prisons, respectively.